2006
DOI: 10.1021/jf0616560
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Shading on Accumulation of Flavonoid Compounds in (Vitis vinifera L.) Pinot Noir Fruit and Extraction in a Model System

Abstract: Accumulation and compositional changes of flavonols, proanthocyanidins, and anthocyanins were measured in Vitis vinifera L. cv. Pinot noir in shaded and exposed treatments. In addition, extraction of these compounds into a model wine solution was measured. The study was conducted in a commercial vineyard within a uniform zone of relatively low vigor vines. Light exclusion boxes were installed on pairs of clusters on the same shoot (shaded treatment), and a second set of clusters on an adjacent shoot were label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
217
4
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(262 citation statements)
references
References 48 publications
(94 reference statements)
40
217
4
1
Order By: Relevance
“…Similar results were also reported in grape berry (Jeong et al, 2004), maize (Singh et al, 1999), bougainvillea (Saifuddin et al, 2010), petunia (Albert et al, 2009) and daisy (Meng et al, 2004). Cortell and Kennedy (2006) have reported the effects of shading on the accumulation of anthocyanins and flavonoids in the Vitis vinifera L. fruit. Several researchers have reviewed that the environmental stimuli like light and temperature play a key role in the regulation of anthocyanins and carotenoid synthesis pathway in the fruits and also flowers (Meng et Guo and Wang, 2010;Azuma et al, 2012).…”
Section: Effects Of Shading Treatmentssupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were also reported in grape berry (Jeong et al, 2004), maize (Singh et al, 1999), bougainvillea (Saifuddin et al, 2010), petunia (Albert et al, 2009) and daisy (Meng et al, 2004). Cortell and Kennedy (2006) have reported the effects of shading on the accumulation of anthocyanins and flavonoids in the Vitis vinifera L. fruit. Several researchers have reviewed that the environmental stimuli like light and temperature play a key role in the regulation of anthocyanins and carotenoid synthesis pathway in the fruits and also flowers (Meng et Guo and Wang, 2010;Azuma et al, 2012).…”
Section: Effects Of Shading Treatmentssupporting
confidence: 83%
“…Also, Meng et al (2004) reported that the red colouration in ray floret of Gerbera hybrid is influenced and controlled by light. The low accumulation and composition of carotenoids and anthocyanin pigments in the overlapped part is due to the shading effect on the bracts (Cortell and Kennedy, 2006;Azuma et al, 2012). …”
Section: Discussion Pigment Analysis During Inflorescence Developmentmentioning
confidence: 99%
“…A few observations have mentioned that high-altitude cultivation strongly alters solar radiation, temperature and other environmental factors around grapevines (Mateus et al, 2002). A higher altitude generally corresponds to stronger sunlight (Cortell & Kennedy, 2006;Fanzone et al, 2010), lower temperature and humidity (Ojeda et al, 2002;Castellarin et al, 2007), greater temperature difference between day and night, and more extreme environmental conditions (Mateus et al, 2001), all of which are important factors affecting the production of flavonoids. Flavonoids, especially anthocyanins and flavonols, are also considered to be effective absorbers of UV-B (Zidorn et al, 2005;Cortell & Kennedy, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…A higher altitude generally corresponds to stronger sunlight (Cortell & Kennedy, 2006;Fanzone et al, 2010), lower temperature and humidity (Ojeda et al, 2002;Castellarin et al, 2007), greater temperature difference between day and night, and more extreme environmental conditions (Mateus et al, 2001), all of which are important factors affecting the production of flavonoids. Flavonoids, especially anthocyanins and flavonols, are also considered to be effective absorbers of UV-B (Zidorn et al, 2005;Cortell & Kennedy, 2006). The abundant UV-B radiation in high-altitude regions could result in the accumulation of anthocyanins and flavonols in grape skins (Cortell & Kennedy, 2006;Fanzone et al, 2010), which have been demonstrated by the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous report also indicated that the shaded treatment had a large increase in glucosides and flavones [8]. But it has not been reported in soybean developing seeds.…”
Section: Introductionmentioning
confidence: 84%